Legal Protection Against Banks As A New Creditural Candidate In Take Over Credit Process - Himawan Sutanto; Hanif Nur Widhiyanti; Istislam Istislam (Faculty of Law, University of Mataram, 2018)
This research journal discusses legal issues relating legal protection of the bank as a prospective new creditor in the process of taking over credit. Where there is no certainty of legal relationship between new creditor candidate with debtor. The Bank as a prospective new creditor can not ensure the release of roya letter on the same day as the binding, so there is no certainty of guarantee status. Bank as a potential creditor becomes a vulnerable party at risk of loss. This study aims to determine and analyze the presence or absence of legal relationship between the bank as a new creditor candidate with the debtor and to know the form of legal protection against the bank as a new creditor candidate in the process of taking over credit that is not in accordance with applicable rules. The research method used by the author is the approach of legislation (statute approach) and case approach (case approach).The absence of a strong legal relationship between the bank as a prospective new creditor with the debtor in the outstanding redemption process, where there is no guarantee of the issuance of the roya letter on the same day during the binding process, in the absence of kepsatian regarding the status of the guarantee, the bank becomes a risky party suffered losses so that the need for a form of legal protection in a preventive and repressive.